Patterns and Impact of Diplomacy Economy in Forum on China- Africa Cooperation (FOCAC) - Indrayani, Irma; Widayanta, Sulistya; ., Suhayatmi (Journal of Posthumanism, 2025)
This study aims to analyze issue political related role of assistance abroad of the People's Republic of China (PRC) to Africa. The PRC looks to be a strong global economy as a result of the success of the fusion of communist ideology and capitalism economics during the Deng Xiaoping era. The idea has open access to international economic markets for the PRC. In order to filling the African market, the PRC formed Forum on China-Africa Cooperation (FOCAC). The institution has done a lot activity cooperation development in Africa. The PRC is utilizing FOCAC as a tools of political diplomacy in the South South cooperation dialogue forum in all field. Infrastructure development economy Africa develop fast. In the FOCAC agreement there are: scheme package credit development capital loan with condition good goods, services and energy Work foreign must originate from the PRC. Governments in African countries are facing risk burden debt term long, while the PRC gained profit net gainer from his position as a creditor country. PRC's success in carrying out international cooperation with Africa has drawn criticism and prejudice. PRC is considered to have deliberately implemented debt date diplomacy through a number of OBOR projects that have turned into debt traps (debt trapped diplomacy) in African countries.